Crowdfunding for unmet medical needs: the case of CAR-T and Gofundme. (13th November 2019) - Toscano, F; Golinelli, D; Guicciardi, S; O'Donnell, E; Rossi, S; Messina, G; Fantini, M P
Abstract: Background: Crowdfunding (CF) is the practice of financing a project by raising money from a large number of people. Many patients use online CF platforms to fund medical needs, whether unmet by their healthcare service - therefore to be sought elsewhere -, or when unable to afford them. CAR-T (Chimeric antigen receptor T-cells) is an innovative therapy approved to treat several types of lymphoma and with potential to treat many other cancers. CAR-T is available in most countries through clinical trials only and its diffusion is limited by high costs. Gofundme is a CF platform 'leader in online medical fundraising'. The objective of this study is to shed some light on the phenomenon of CF for CAR-T therapy, describing the campaigns started on Gofundme. Methods: We extracted data from CAR-T campaigns started in Europe and publicly available on Gofundme until March 2019. Data related to each campaign has been analyzed and reported through descriptive analyses. Results: Since 2017, 26 CAR-T treatment campaigns have been started. Due to the privacy policy of the platform, we were able to retrieve data from only 12 of them; 3 campaigns were closed, thus not disclosing enough data to be included. Nine campaigns were studied: 4 from Italy, 4 from the UK, 1 from Spain. The United States were the main destination. The median campaign goal was 180k€. The number of campaign shares on social media and the percentage of goal raised seemed to be linked. Conclusions: CF is unquestionably a good expression of the Internet: it channels empathy towards important causes, providing tangible help. However, when applied to healthcare - especially to experimental treatments -, several questions arise. Patients affected by treatment resistant cancers may be prone trying new treatments to keep the hope alive, even when indication is missing or scientific evidence is lacking. Policymakers should monitor healthcare related CF campaigns, both for equity and safety reasons. Key messages: Policymaker should monitor healthcare related CF campaigns, both for equity and safety reasons. Healthcare related crowdfunding campaigns could be interpreted as an indicator of unmet medical needs.